Multicomponent T2 analysis of articular cartilage with synovial fluid partial volume correction. Issue 5 (5th October 2015) - Liu, Fang; Chaudhary, Rajeev; Block, Walter F.; Samsonov, Alexey; Kijowski, Richard
Abstract : Purpose: To investigate the use of a three‐pool model to account for the confounding effects of synovial fluid on multicomponent T 2 analysis of articular cartilage using Multicomponent Driven Equilibrium Single Shot Observation of T 1 and T 2 (mcDESPOT). Materials and Methods: mcDESPOT was performed on the knee of eight asymptomatic volunteers and eight patients with osteoarthritis at 3.0T with multicomponent T 2 maps created using the two‐pool model and a three‐pool model containing a nonexchanging synovial fluid water pool. The fraction of the fast‐relaxing water component (FF ) and the T 2 relaxation times for the fast‐relaxing ( T 2F ) and slow‐relaxing ( T 2S ) water components were measured in the superficial and deep layers of patellar cartilage using the two‐pool and three‐pool models in asymptomatic volunteers and patients with osteoarthritis and were compared using Wilcoxon signed rank tests. Results: Within the superficial layer of patellar cartilage, FF was 22.5% and 25.6% for asymptomatic volunteers and 21.3% and 22.8% for patients with osteoarthritis when using the two‐pool and three‐pool models, respectively, while T 2S was 73.9 msec and 62.0 msec for asymptomatic volunteers and 72.0 msec and 63.1 msec for patients with osteoarthritis when using the two‐pool and three‐pool models, respectively. For both asymptomatic volunteers and patients with osteoarthritis, the two‐pool model provided significantly ( P < 0.05) lower FF and higher T 2S than the three‐pool model, likely due to the effects of synovial fluid partial volume averaging. Conclusion: The effects of partial volume averaging between superficial cartilage and synovial fluid may result in biased multicomponent T 2 measurements that can be corrected using an mcDESPOT three‐pool model containing a nonexchanging synovial fluid water pool. J. Magn. Reson. Imaging 2016;43:1140–1147.